Envelhecimento acelerado de sementes de espécies oleráceas - Barbosa, Rafael Marani [UNESP]; da Costa, Denis Santiago; de Sá, Marco Eustáquio [UNESP] (My University, 2011)
The quality of seeds used in the agricultural production process is one of the main factors considered for the development of a crop. This study investigated the effect of vigor level in the performance of six oleraceous species seeds. Commercial seeds of lettuce, eggplant, broccoli, cauliflower, rocket, and tomato were subjected to accelerated aging, for 48 and 72 hours, to obtain lots with three vigor levels, resulting in one regular lot and two lots aged for different periods. After that, the seeds were submitted to germination tests, electrical conductivity, seedling emergence in trays, seedling length and dry weight. The effect of accelerated aging becomes stronger when the exposure time of seeds to high air relative humidity and temperature increases. This exposure reduces more emphatically the seed quality for some species, such as lettuce, cauliflower, and rocket, than for others, such as broccoli, tomato and eggplant. Less vigorous seeds, in addition to lower germination and emergence, show delays in the seedling formation process.
Accelerated aging of oleraceous species seeds
Keywords: Asteraceae; Brassicaceae; Physiologic potential; Solanaceae; Vegetables